Analisis Yuridis Akta Kesepakatan Dalam Transplantasi Ginjal Antara Calon Donor Dan Resipien (Tinjauan Dari Perspektif Hukum Indonesia): Legal Analysis Of The Deed Of Agreement In Kidney Transplantation Between Prospective Donor And Recipient (Review From Indonesian Legal Perspective) - Sofiana; Jamiatur Robekha; Yasarman (Universitas Medan Area, 2025)
This study aims to analyze organ transplantation, especially the transfer of organs from living donors to recipients, which is one of the main therapies for patients with chronic kidney failure which aims to restore the patient's quality of life. In Indonesia, the implementation of organ transplantation still relies on living donors and has been regulated in laws and regulations that include provisions regarding the implementing hospital, the implementing medical team, and the advocacy team. The advocacy team plays a role in ensuring that the transplantation process runs without elements of commercialization and exploitation, and guarantees the fulfillment of the rights and obligations of prospective donors and their families. The legal problems that arise are how the legality and strength of the evidentiary deed of agreement between the donor and recipient as written evidence, and how it is protected in preventing illegal practices such as organ trafficking. This study uses a normative juridical method with a statutory regulatory approach and legal document studies, and is analyzed qualitatively. The results of the study indicate that the deed of agreement has a strategic position as valid legal evidence, as well as an instrument of ethical and legal protection for all parties involved in the transplant procedure. Therefore, a properly drafted deed of agreement not only fulfills the formal legal aspects, but also plays an important role in maintaining the integrity of the organ transplantation process in Indonesia.